IEEE INFOCOM '99. Conference on Computer Communications. Proceedings. Eighteenth Annual Joint Conference of the IEEE Computer A 1999
DOI: 10.1109/infcom.1999.749308
|View full text |Cite
|
Sign up to set email alerts
|

Quality of service driven packet scheduling disciplines for real-time applications: looking beyond fairness

Abstract: In this paper we focus on real-time scheduling of "soft" realtime data services such as multimedia data, MPEG video streaming and IP telephony, which can tolerate a small degree of loss or delay. We argue that network operators and service providers should be able to select from a range of Quality of Service objectives, including maximizing the number of customers receiving good service. Further, we argue that scheduling disciplines such as fair queueing are unable to achieve such goals and hence there is a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…In [35] it is suggested that the fairness is not the best solution and that better results can be obtained by trying to maximize the number of stations whose QoS needs are covered.…”
Section: Maximum Stations Qos Achieving Based For Pcfmentioning
confidence: 99%
“…In [35] it is suggested that the fairness is not the best solution and that better results can be obtained by trying to maximize the number of stations whose QoS needs are covered.…”
Section: Maximum Stations Qos Achieving Based For Pcfmentioning
confidence: 99%
“…It was shown to outperform other scheduling policies with the presence of two queues. Most importantly, [7,13] show the dual queue model, from which this work is extended, to again provide greater QoS than Round Robin, Fair Queueing and FIFO policies.…”
Section: Introductionmentioning
confidence: 98%
“…The dual queue was introduced in [7] as a device to improve the quality of service (QoS) of customers in communication networks. The dual queue consists of two sub-queues, denoted by queue 1 (the primary queue) and queue 2 (the secondary queue).…”
Section: Introductionmentioning
confidence: 99%
“…Packet scheduling is a crucial technique for performing resource allocation to bring about QoS and service differentiation [6]. Recently, the QoS research community has started considering the concept of relative and proportional differentiated services [7], [8], which are simpler to implement compared to absolute differentiated services.…”
Section: Introductionmentioning
confidence: 99%